Investigating the role of Small G Proteins in the activation of p38 MAPK by Interleukin-1 - McDermott, Eva Margareta Pålsson (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2001)
This study is an investigation into the role of small G proteins in IL-1 signalling. Lethal Toxin, from Clostridium sordellii, which specifically glucosylates and thereby inactivates the low molecular weight G proteins Ras, Rap, Rac, and Ral, inhibited the activation of p38 and p42/p44 Mitogen Activated Protein Kinase (MAPK) by IL-1 in EL4.N0B-1 cells and primary fibroblasts. C. difficile Toxin B, which inhibits Rac, Rho, and Cdc42 had no effect on the activation of p38 and p42/p44 MAPK by IL-1 which indicated that LT was probably targeting a Ras-family G protein on the IL-1 pathway. LT glucosylated proteins of molecular weights 18,19 and 23 kDa to an extent that correlated with the inhibition of the activation of p38 MAPK by IL-1. In addition, LT failed to inhibit p38 MAPK activation by IL-1 in a UDP-glucose deficient cell line, indicating that glucosylation of small G proteins was required for the inhibitory effect. These studies indicate that an LT-sensitive small G protein, possibly belonging to the Ras subfamily, play a critical role in IL-1 signalling.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin